Marriage and Family Formation in the Contemporary Manggaraian Culture (Flores, Indonesia) - Gunawan, Vinsensius Adi (Studia Warmińskie, 2022)
Indonesia, although it is developing rapidly, still offers many traditional circumstances that could be the subject of research. An example is Manggarai, a region in the western part of Flores Island. When founding a family, the inhabitants of Manggarai still practice the traditional way (adat).This procedure is based on the local concept that the family not only has a classical meaning as a nuclear family, called kilo, ca kilo or mbaru kilo), but also includes a much wider circle. This is why every path in the process of marriage becomes so urgent, which potentially creates a new relationship of two larger families (woe nelu). These circumstances play an important role in the social and political life of the Manggaraians, even when they live apart from their homeland.